1994
DOI: 10.1017/s0730938400018384
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Interpretations of “Acid Rain” and the Construction of Scientific Uncertainty in Political Settings

Abstract: Much research in social studies of science addresses scientists' interpretative flexibility in the construction of scientific knowledge. This flexibility is readily visible among different scientists' competing knowledge-claims as well as in their accounts across different social settings. This article illustrates this process and discusses some of its implications through a case study of descriptions of acid rain in published scientific papers and Congressional testimony. As acid rain was flexibly reconstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The regulation of the new agricultural-environmental biotechnology is an example of how politics and science intertwine in policymaking. While politics plays a key role in other science policy arenas, such as acid rain (Zehr, 1994), alachlor, alar, asbestos, and radon (Harrison and Hoberg, 1994), what makes the new agricultural-environmental biotechnology so intriguing is that it is the first technology to be regulated before catastrophic risk has been proven (Hardy and Glass, 1985;Krimsky and Wrubel, 1996:233). Additionally, and perhaps more so than for any previous technology, regulatory triggers depend on the definition of what is natural and what is man-made, definitions that have been highly contested in policy debate.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of the new agricultural-environmental biotechnology is an example of how politics and science intertwine in policymaking. While politics plays a key role in other science policy arenas, such as acid rain (Zehr, 1994), alachlor, alar, asbestos, and radon (Harrison and Hoberg, 1994), what makes the new agricultural-environmental biotechnology so intriguing is that it is the first technology to be regulated before catastrophic risk has been proven (Hardy and Glass, 1985;Krimsky and Wrubel, 1996:233). Additionally, and perhaps more so than for any previous technology, regulatory triggers depend on the definition of what is natural and what is man-made, definitions that have been highly contested in policy debate.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent science issues such as stem cell research, global warming, and new advances in biotechnology bring with them controversy, which affects the structure of scientific news (Dunwoody, 1999;Nelkin, 1995;Nisbet et al, 2003;Nisbet & Lewenstein, 2002;Rogers, 1999;Zehr, 1994Zehr, , 2000. These issues spark moral and political debates, and have resulted in a change in scientific reporting.…”
Section: Sourcing and Science Reportingmentioning
confidence: 99%
“…The history of acid rain policy making in Western Europe as well as in North America has been widely reconstructed and studied from a variety of angles, some within a perspective shared by this paper (Roqueplo, 1988;Regens and Rycroft, 1988;Park, 1989;Boehmer-Christiansen and Skea, 1991;Forster, 1993;Zehr, 1994aZehr, , 1994bHajer, 1995;Herrick and Jamieson, 1995;Tessier, 1996;Mutton, 1998). That of climate change policy making is fast emerging (Brunner, 1991;Ungar, 1992;Jamieson, 1992;Boehmer-Christiansen, 1993;Hart and Victor, 1993;Roqueplo, 1995;Shackley andWynne, 1995, 1996;O'Riordan and Jäger, 1996;Timmerman, 1996;Fernmann, 1997;Weart, 1997).…”
Section: Acid Rain and Climate Change In Canada: Contrasting Discoursesmentioning
confidence: 99%
“…The purpose of this paper is to address the question of how social actors respond to ecological problems and what kind of discourse they construct. Many writers and studies have shown that in environmental matters science is a necessary and critical variable, but not always the determining factor in formulating policies (Benedick, 1991;Zehr, 1994a;Lanchberry and Victor, 1995). Moreover, the science itself, which serves as a necessary basis for decision and policy, is most often reviewed severely, contested, or judged insufficient for action.…”
Section: Introductionmentioning
confidence: 99%